Reconsidering the Stolper–Samuelson Theorem: Empirical Evidence from Developing Countries - Çelik, Onur (Ekonomika, 2026)
Studies measuring the impacts of the COVID-19 pandemic remain limited in the empirical literature. For this reason, this study estimated the determinants of income distribution for labor and non-labor production factors in the period 2014-2022 within the framework of the Stolper-Samuelson (SS) Theorem. Regarding the sample and methodology, developing and labor-intensive countries were selected, and panel data analysis was employed. The results indicated that income distribution in the reference countries changed in the disadvantage of the labor factor. In addition, the inflation rate also declined the income share of labor in the Gross Domestic Product. Contrary to this, while trade openness and inflation data increased the income share of other production factors; no significant effect was found from foreign direct investments. Although the findings did not fully support the Theorem, they aligned with the realities of an exceptional period. Therefore, to protect labor welfare during inflationary periods, it is recommended that economic policies consider the relative income share of labor, while taking its real value into account.
Keywords: The Stolper Samuelson Theorem; Income Distribution; Covid-19 Outbreak; Trade Openness; Developing Countries